EP.WE.718An audit of the photographic documentation of upper gastrointestinal endoscopy at Cork University Hospital. (28th October 2021) - O'Brien, Stephen; Foley, Niamh; Murphy, Amy Edwards; McCourt, Morgan; Killeen, Shane; Andrews, Emmet
Abstract: Introduction: A joint statement by the British Society of Gastroenterology and the Association of Upper Gastrointestinal Surgeons in 2017 recommended that photographic documentation of relevant anatomical landmarks should be a Key Performance Indicator of oesophagogastroduodenoscopy (OGD). The aim of this study was to assess this photodocumentation standard among surgeons and gastroenterologists in a tertiary referral centre. Methods: Cork University Hospital endoscopy unit records were examined for a 2-month period from 01/10/20-27/11/20. OGDs were performed by 3 consultant colorectal surgeons and 4 consultant gastroenterologists over the time period. Demographic data and photodoumentation information were obtained from the Endoraad GI reporting tool. Surgeons and gastroenterologists performances was compared using the chi-squared test. Results: 104 OGDs were analysed. Fifty-three (51%) OGDs were performed in women and 51(49%) OGDs were performed by surgeons. The documentation for each site was; gastro-oesophageal junction- 68% (69/102), fundus on retroflexion- 71% (72/102), gastric body- 32% (33/102), antrum- 61% (62/102), and duodenal bulb- 35% (36/102), without significant differences (p > 0.05) for these sites between surgeons and gastroenterologists. There was more documentation of the upper oesophagus by surgeons (31% vs.12%, p = 0.030) and there was more documentation of the distal duodenum by gastroenterologists (90% vs.47%, p < 0.01). Pictures were unable to be saved in two patients due to technical failure. Discussion: Photodocumentation is increasingly important from a medico-legal viewpoint. There is room for improvement in our centre, but these rates are comparable to other published series. An educational session is being planned and following this adherence to photodocumentation standards will be re-examined.